PERCEPTUAL STUDY OF PLASTIC WASTE BRICKS FOR SHARIA APARTMENT IN INDONESIA - Muhammad Mutammam Musthofa; Rully Damayanti (Petra Christian University, 2022)
Bricks from plastic waste have the potential to become the wall material for apartment units because they are lightweight and have an interlock system that makes it easy to dismantle and reuse. Sharia Apartments in Indonesia exist because of the market potential for the majority of Muslims who are interested in a halal lifestyle. This article identifies Muslim perceptions of the application of bricks from plastic waste to sharia apartment residential units. The perception is carried out by comparing three plastic waste brick product companies. The method used is through questionnaires and interviews based on regional demographics. It was found that brick of plastic waste can be received positively by Muslim respondents, but its use is limited to particular spaces to avoid negative perceptions.